2020
DOI: 10.17533/udea.iee.v38n1e04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Interactive Training on Choosing Delivery Method among Primiparous Pregnant Women: An Interventional Study

Abstract: Objective. To evaluate the effect of interactive training conducted during pregnancy on choosing delivery method among primiparous women. Methods. Quasi-experimental study carried out in 2017 in two hospitals in the city of Bushehr (Iran), with the participation of 108 primiparous pregnant women in an educational program consisting of eight 2-hour sessions every two weeks in which interactive training activities were performed (group discussions, classroom sessions, and delivery of printed educational material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…The 133 included studies collectively reported on more than 9.1 million surgical procedures (median per study, 894 [IQR, 97-4259]) and more than 11.4 million participants (median per study, 989 [IQR, 257-6857]) from 63 LMICs . Of all 133 LMICs, we found studies from 15 of all 29 low-income countries (51.7%), 25 of all 50 lower-middle–income countries (50.0%), and 23 of all 55 upper-middle–income countries (41.8%) . Fourteen studies (10.5%) were multinational …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 133 included studies collectively reported on more than 9.1 million surgical procedures (median per study, 894 [IQR, 97-4259]) and more than 11.4 million participants (median per study, 989 [IQR, 257-6857]) from 63 LMICs . Of all 133 LMICs, we found studies from 15 of all 29 low-income countries (51.7%), 25 of all 50 lower-middle–income countries (50.0%), and 23 of all 55 upper-middle–income countries (41.8%) . Fourteen studies (10.5%) were multinational …”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies (10.5%) were multinational . Of the 119 studies (89.5%) originating from single countries, 69 (58.0%) were from upper-middle–income countries and 30 (25.2%) were from East Asia and the Pacific (Table 1 and Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations